A case of oculo‐cerebral B‐cell lymphoma in a cat. (23rd April 2012) - Giordano, Cristina; Giudice, Chiara; Bellino, Claudio; Borrelli, Antonio; D'Angelo, Antonio; Gianella, Paola
Abstract Purpose To describe a case of a cat with primary B‐cell lymphoma affecting the eye and brain and which shared features similar to oculo‐cerebral lymphoma in humans. Methods A 13‐year‐old castrated male Persian cat presented with clinical signs of anterior uveitis and increased intraocular pressure (IOP) in the left eye (OS). A complete diagnostic work‐up was declined, and left‐eye enucleation was performed. The globe was submitted for histopathology. One week after surgery, the cat became inappetent, hypothermic, and aggressive. Euthanasia was requested by the owner, and a necropsy was permitted. Results Histopathology of the enucleated globe revealed an extensive neoplastic infiltration consistent with large‐cell lymphoma, affecting the anterior uvea, neuroretina and optic nerve. At necropsy, all organs were unremarkable except for the brain, where there was a neoplastic cell population consistent with that described in the left eye, infiltrated and expanded meninges, and perivascular spaces. Immunohistochemically, the neoplastic cells were positive for B‐cell marker (CD20) and negative for T‐cell marker (CD3). Histology and immunophenotyping suggested a diagnosis of primary central nervous system and ocular large B‐cell lymphoma. Discussion The lymphoma in this cat resembled oculo‐cerebral lymphoma in humans, sharing similar clinical features and histopathological findings, including the perivascular pattern of neoplastic cell infiltration. To the best of the authors' knowledge, this is the first description of a primary oculo‐cerebral B‐cell lymphoma in a cat.